Assessment of cardiovascular risks in women and current preventive approaches in nursing - Olgun, Nermin; Bayındır Çevik, Ayfer; Çevik, Ayfer Bayındır (My University, 2015)
[Abstract Not Available]
Keywords: Cardiovascular; Risk management; Lifestyle changes; Risk reduction; Nursing; Kardiyovasküler; Risk yönetimi; Yaşam tarzı değişiklikleri; Risk azaltma; Hemşirelik